Optimalisasi Potensi Pisang: Pemberdayaan Ekonomi Ibu Rumah Tangga di Dusun Berambang, Desa Batu Putih, Kecamatan Sekotong - Vidya Yanti Utami; Nidya Putri Syahida; Nasruddin Nasruddin; Fitriah Kartini (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Berambang Hamlet, located in Batu Putih Village, Sekotong Subdistrict, possesses abundant agricultural potential in the form of bananas. However, their utilization remains limited to simple processing, such as fried bananas, which offer low economic value. The housewives in this hamlet express a strong desire to develop more diverse and economically valuable banana-based products, but they face challenges due to limited skills in production, packaging, and marketing. This community service initiative aims to enhance the economic capacity of housewives through technical training in banana processing, product packaging, and effective marketing strategies. The methods applied include participatory observation, focused group discussions, hands-on practical training, and ongoing mentoring. The results of this activity indicate a significant improvement in participants' skills, particularly in processing bananas into products such as flavored banana chips. Additionally, participants are now able to design attractive packaging and market their products both locally and through digital platforms. This initiative has also succeeded in fostering new awareness of household economic potential and has encouraged entrepreneurial spirit within the community. Thus, the program not only provides short-term benefits in the form of increased skills but also creates sustainable economic opportunities for the residents of Berambang Hamlet. This capacity-building effort is expected to serve as a starting point for the development of micro-enterprises based on local potential, thereby contributing to improved family welfare and strengthening the village economy.